Propuesta de aprovechamiento de tomate chonto en polvo deshidratado como alternativa de valor agregado en la finca tomates Don Beto (2023)
His degree work presents the technical evaluation for the development of the use- of the Chonto tomato in its fourth and fifth categories, which is regularly wasted as animal feed, but at the same time shows a great opportunity for value generation and transformation into other consumer products. The proposal starts by determining the volume of raw material available on the farm - Don-Beto tomatoes and establishing the yield and capacity margins that the project will have for the processing of said raw material.